Adjuvant locoregional radiation therapy in breast cancer patients with pathologic complete response after neoadjuvant chemotherapy: A systematic review and meta-analysis. (March 2022) - Nikyar, Normehr; Tegnelius, Eva; Valachis, Antonis
Graphical abstract: Highlights: Adjuvant locoregional radiation therapy (LRRT) is standard of care in pN+ breast cancer. Adjuvant LRRT in pN0 after neoadjuvant chemotherapy (NACT) is controversial. Thirteen studies were found to be eligible to a meta-analysis. Adjuvant LRRT seems to almost halve the risk for locoregional recurrence. No improvement in disease-free or overall survival was observed. The current level of evidence is low. Abstract: Purpose: The aim of the present meta-analysis was to investigate the impact of adjuvant locoregional radiation therapy (LRRT) in breast cancer patients with clinical lymph node metastatic disease achieving ypN0 after neoadjuvant chemotherapy (NACT). Materials and methods: A systematic review of studies on PubMed was performed. A meta-analysis was conducted by computing extracted hazard ratios (HRs) and 95% confidence intervals (CIs) into a fixed-effects model. Results: Thirteen studies were included in the meta-analysis. Adjuvant LRRT significantly reduced the risk of locoregional recurrence (LRR) in patients with N+ at diagnosis and ypN0 (HR 0.59; 95% CI 0.42–0.81). However, no statistically significant difference on disease-free survival (DFS) or overall survival (OS) was found. Conclusions: LRRT significantly reduced the risk of LRR in patients with ypN0 after NACT whereas no impact on DFS or OS was observed. The low level of evidence should be considered when interpreting the results in clinical practice.